Mild cognitive impairment and dementia reported by former professional football players over 50 yr of age: An NFL-LONG Study - Walton, S. R.; Brett, B. L.; Chandran, A.; DeFreese, J. D.; Mannix, R.; Echemendia, R. J.; Meehan III, W. P.; McCrea, M.; Guskiewicz, K. M.; Kerr, Z. Y. (Medicine & Science in Sports & Exercise, 2022)
Purpose This study aimed to estimate prevalence of mild cognitive impairment (MCI) and dementia diagnoses in former National Football League (NFL) players =50 yr old and examine the relationships among these diagnoses and an array of predictors of long-term brain health.